Zmiany w planowaniu działań marketingowych dużych przedsiębiorstw w Polsce w latach 2001-2005 - Kowal, Witold (Changes in the Marketing Planning in Polish Firms in Years 2001-2005, 2007)
The presentation aims to address the problem of marketing planning in Polish companies. In the years 2001-2005 there could be seen an increase in the participation of companies realizing offensive strategies and planning their own marketing operations on the ground of company strengths. Such behaviour of Polish companies can be explained as a result of the accession of Poland to the European Union.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1170, s. 86-95